APPLICATION OF BLENDED LEARNING ON OPEN JUNIOR HIGH SCHOOL IN INDONESIA - jhoni lagunsiang (International Journal of Education, Information Technology, and Others, 2018)
The purpose of this study is to investigate the implementation of blended learning in the Open Junior High School in Indonesia. This research is quantitative descritive survey method. Primary data were obtained through questionnaires. The study sample consisted of students and teachers drawn from Cirebon regency. This research was conducted during June to December 2015. The results showed that: In planning the self-study, there were 16.7% of teachers said always to plan, 50% said often, 33% said sometimes, and none of the states rarely and never. In planning face to face, as much as 43.8% of teachers said always to plan, 50% said often, 6.3% said sometimes, and nothing that states rarely and never. But in planning online learning, as much as 12.5% of teachers said always to plan, 37.5% said often, 50% said sometimes, and nothing that states rarely and never. Implementation of blended learning in the Open Junior High School in Indonesia starting from the planning, implementation and evaluation of good.